A bibliometric analysis of the recent advances in diazepam from 2012 to 2021 - Zhang, Ming; Kou, Lin; Qin, Yaya; Chen, Junwen; Bai, Dazhang; Zhao, Li; Lin, Hongyu; Jiang, Guohui (Frontiers in Pharmacology, 2022)
Background: Diazepam is a classic benzodiazepine drug that has been widely used for disorders such as anxiety, sleep disorders, and epilepsy, over the past 59 years. The study of diazepam has always been an important research topic. However, there are few bibliometric analyses or systematic studies in this field. This study undertook bibliometric and visual analysis to ascertain the current status of diazepam research, and identify research hotspots and trends in the past 10 years, to understand future developments in basic and clinical research. Methods: Articles and reviews of diazepam were retrieved from the Web of Science core collection. Using CiteSpace, VOSviewer, and Scimago Graphica software, countries, institutions, authors, journals, references, and keywords in the field were visually analyzed. Results: A total of 3870 publications were included. Diazepam-related literature had high volumes of publications and citations. The majority of publications were from the USA and China. The highest number of publications and co-citations, among the authors, was by James M Cook. Epilepsia and the Latin American Journal of Pharmacy were the journals with the largest publication on diazepam and Epilepsia was the most frequently cited journal. Through a comprehensive analysis of keywords and references, we found that current research on diazepam is focused on its mechanism of action, application in disease, pharmacokinetics, risk, assessment and management of use, status epilepticus, gamma-aminobutyric acid receptors (GABAR), intranasal formulation, gephyrin, and that ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) is the current research hotspot. Conclusion: Research on diazepam is flourishing. We identified research hotspots and trends in diazepam research using bibliometric and visual analytic methods. The clinical applications, mechanisms of action, pharmacokinetics, and assessment and management of use of diazepam are the focus of current research and the development trend of future research.